2012
DOI: 10.1007/s11999-012-2278-7
|View full text |Cite
|
Sign up to set email alerts
|

Reason for Revision Influences Early Patient Outcomes After Aseptic Knee Revision

Abstract: Background Revision TKA less consistently produces improvements in clinical function and quality of life when compared with primary TKA. The reasons for this difference are unclear. Questions/purposes We determined differences in patientreported outcomes and rates of satisfaction between primary and revision TKAs, and determine whether the reason for revision influences patient-reported outcomes after revision TKA. Methods We retrospectively analyzed prospectively collected patient-reported outcome measures (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
69
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 25 publications
18
69
0
1
Order By: Relevance
“…Despite similar or better function and pain scores for patients undergoing a revision surgery than for those undergoing a primary joint surgery, a revision surgery does not seem to bring as much pain and functional improvement 12 months later. This finding is congruent with the existing literature 351,352 and needs to be kept in mind when patients and clinicians discuss post-surgical expectations.…”
Section: Measuring Functional Outcomes In Patients Having Hip and Knesupporting
confidence: 90%
“…Despite similar or better function and pain scores for patients undergoing a revision surgery than for those undergoing a primary joint surgery, a revision surgery does not seem to bring as much pain and functional improvement 12 months later. This finding is congruent with the existing literature 351,352 and needs to be kept in mind when patients and clinicians discuss post-surgical expectations.…”
Section: Measuring Functional Outcomes In Patients Having Hip and Knesupporting
confidence: 90%
“…It emphasizes the growing appreciation that patient satisfaction and associated functional outcomes are heavily dependent upon the reason for implant revision. This finding is consistent with previous reports from independent series [6] and a recent registry analysis of patient reported outcome data [1]. These studies, along with the work of van Kempen and colleagues, reveal that functional outcomes are best when revision is performed for a single, well-defined nonseptic cause.…”
supporting
confidence: 90%
“…Ong et al [11] showed that a RTKA has a 5 to 6 times increased risk of re-revision. In a recent study, Baker et al [12] showed that improvement after a RTKA was only 69%-76% of a primary TKA and that the Medicare database showed the 5-year survivorship of RTKA to be only 87%.…”
Section: Discussionmentioning
confidence: 99%